Syncretism and Identity: The case of the Virgen de Matanzas as a didactic resource for the teaching of intangible cultural heritage - Hernández de la Cruz, José Manuel (Clio. History and History Teaching, 2019)
Popular religiosity is one of the most evident manifestations in the values of the societies and an important and recurrent form of expression of the intangible cultural heritage. It transforms and evolves along with the social developments and plays an important role in the spread of cultural knowledge. It is, at the same time, a cardinal didactic instrument in the teaching of the history and the heritage that is linked to it. The objective of this article is to demonstrate the educational value and importance of the intangible cultural heritage, the need for its study, preservation, and dissemination of the material components that are integral in it, through an event linked to popular religiosity, of great significance and unprecedented in Matanzas culture.